Neurolin, a cell surface glycoprotein on growing retinal axons in the goldfish visual system, is reexpressed during retinal axonal regeneration (The Rockefeller University Press, 1992)
The mAb E 21 recognizes a cell surface glycoprotein selectively associated with fish retinal ganglion cell axons that are in a state of growth. All retinal axons and ganglion cells in goldfish embryos stained for E 21. In adult fish, however, E 21 immunoreactivity exhibited a patterned distribution in ganglion cells in the marginal growth zone of the continuously enlarging fish retina and the new axons emerging from these cells in the retina, optic nerve, and optic tract. The E 21 antigen was absent from older axons, except the terminal arbor layer in the tectum, the Stratum fibrosum et griseum superficiale where it was uniformly distributed. Upon optic nerve transection, the previously unlabeled axons reacquired E 21 positivity as they regenerated throughout their path to the tectum. Several months after ONS, however, E 21 staining disappeared from the regenerated axons over most of their lengths but reappeared as in normal fish in the terminal arbor layer. The immunoaffinity-purified E 21 antigen, called Neurolin, has an apparent molecular mass of 86 kD and contains the HNK1/L2 carbohydrate moiety, like several members of the class of cell adhesion molecules of the Ig superfamily. The NH2-terminal amino acid sequence has homologies to the cell adhesion molecule DM-Grasp recently described in the chicken. Thus, retinal ganglion cell axons express Neurolin during their development and are able to reexpress this candidate cell adhesion molecule during axonal regeneration, suggesting that Neurolin is functionally important for fish retinal axon growth.